2021
DOI: 10.1002/adfm.202009359
|View full text |Cite
|
Sign up to set email alerts
|

Processable High Electron Mobility π‐Copolymers via Mesoscale Backbone Conformational Ordering

Abstract: The synthesis and experimental/theoretical characterization of a new series of electron‐transporting copolymers based on the naphthalene bis(4,8‐diamino‐1,5‐dicarboxyl)amide (NBA) building block are reported. Comonomers are designed to test the emergent effects of manipulating backbone torsional characteristics, and density functional theory (DFT) analysis reveals the key role of backbone conformation in optimizing electronic delocalization and transport. The NBA copolymer conformational and electronic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…49,50 Furthermore, in the solution state, the 0–0 vibration peak are stronger than 0–1 vibration peak, which according to the H , J -aggregation model for organic semiconductor, can be ascribed to a stronger J -type intrachain coupling. 33 It is worth noting that the 0–0/0–1 intensity ratio has changed slightly in the film state, and an increase in the intensity of the 0–1 vibrational peak was observed in the film state spectrum of P(T-TzII-T-DPP)-C12 , which may indicate a relatively increased H -type aggregation character in the film state. A similar observation was made in P(Se-TzII-T-DPP)-C12 and P(Se-TzII-T-DPP)-C20 (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…49,50 Furthermore, in the solution state, the 0–0 vibration peak are stronger than 0–1 vibration peak, which according to the H , J -aggregation model for organic semiconductor, can be ascribed to a stronger J -type intrachain coupling. 33 It is worth noting that the 0–0/0–1 intensity ratio has changed slightly in the film state, and an increase in the intensity of the 0–1 vibrational peak was observed in the film state spectrum of P(T-TzII-T-DPP)-C12 , which may indicate a relatively increased H -type aggregation character in the film state. A similar observation was made in P(Se-TzII-T-DPP)-C12 and P(Se-TzII-T-DPP)-C20 (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…3, it can be seen clearly that the trimer adopts a perfect linear coplanar conformation (both from the top view and from the side view), and has an even HOMO and LUMO orbital distribution along all of the repeating units, which is also well known to facilitate more efficient interchain coupling interaction. 33,44 Overall, theoretical calculations predict that the copolymer of T-TzII and T-DPP has an ideal coplanar molecular backbone, suitable HOMO/LUMO energy levels, long-range orbital distribution of HOMO/LUMO along the polymer chain and strong dipole–dipole interaction, all beneficial for high and balanced ambipolar charge transport.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two copolymers (P63a and P63b) based on the NBA and 2FBT moieties with different F atoms (0 and 2F) were synthesized. [ 152 ] After introduction of F atoms into the benzothiadiazole, the HOMO energy level of P63b was lowered to −5.92eV, which was 0.35 lower than that of P63a. GIXRD characterization indicated that the fluoropolymer P63b adopted both edge‐on and face‐on orientations, whereas P63a only formed a face‐on orientation.…”
Section: Improving the Electron Transport Of D–a‐type Sps Via Amsmentioning
confidence: 99%
“…Recent researches on donor-acceptor copolymer semiconductors reporting high mobility have shown that the degree of crystallinity does not directly correlate with the performance of polymer semiconductors. [31][32][33][34] This means that even in a polymer semiconductor with low crystallinity, efficient charge transport can be realized when sufficient tie chains are linked between small-localized aggregations. Utilizing a semi-paracrystalline polymer semiconductor in a photochromic hybrid system can simultaneously manifest high mobility and photoprogramming characteristics, which were considered before as a trade-off in previous polymer semiconductor/DAE hybrid systems.…”
Section: Introductionmentioning
confidence: 99%